Interpretation of the Study Of Formation of Communicative Competence - S.A. Khodjabekova (Genius Journals, 2023)
Already in the first years of gaining independence by our republic, the education and upbringing of children became one of the priorities of the state policy in the field of education. In accordance with this, the issues of education and upbringing of children with special needs, the need for further improvement in this area are reflected in a number of laws and regulations. In the implementation of the requirements outlined in the documents, the task of developing communicative competence among preschoolers is of particular relevance.
Keywords: Pedagogy; inclusive education; hospital pedagogy